\[\boxed{\text{604\ (604).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[Пусть\ числа\ n\ и\ (n + 1),\ тогда:\]
\[\left( n^{2} + (n + 1)^{2} \right) - 2n \cdot (n + 1) =\]
\[= n^{2} + n^{2} + 2n + 1 - 2n^{2} - 2n =\]
\[= 1 \Longrightarrow\]
\[\Longrightarrow не\ зависит\ от\ n.\]
\[\boxed{\text{604.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[n^{3} + 3n^{2} + 2n =\]
\[= n \cdot \left( n^{2} + 3n + 2 \right) =\]
\[= n \cdot \left( n^{2} + 2n + n + 2 \right) =\]
\[= n \cdot ((n \cdot (n + 1) + 2 \cdot (n + 1) =\]
\[= n \cdot (n + 1) \cdot (n + 2) -\]
\[последовательные\ \]
\[натуральные\ числа,\ \]
\[следовательно,\ одно\ кратно\ 2,\ \]
\[другое\ кратно\ 3,\ тогда\ \]
\[произведение\ кратно\ 6.\ \]
\[Что\ и\ требовалось\ доказать.\]